Patient blood management during the COVID–19 pandemic: a narrative review. (6th May 2020) - Baron, D. M.; Franchini, M.; Goobie, S. M.; Javidroozi, M.; Klein, A. A.; Lasocki, S.; Liumbruno, G. M.; Muñoz, M.; Shander, A.; Spahn, D. R.; Zacharowski, K.; Meybohm, P.
Summary: As COVID–19 disease escalates globally, optimising patient outcome during this catastrophic healthcare crisis is the number one priority. The principles of patient blood management are fundamental strategies to improve patient outcomes and should be given high priority in this crisis situation. The aim of this expert review is to provide clinicians and healthcare authorities with information regarding how to apply established principles of patient blood management during the COVID–19 pandemic. In particular, this review considers the impact of the COVID–19 pandemic on blood supply and specifies important aspects of donor management. We discuss how preventative and control measures implemented during the COVID–19 crisis could affect the prevalence of anaemia, and highlight issues regarding the diagnosis and treatment of anaemia in patients requiring elective or emergency surgery. In addition, we review aspects related to patient blood management of critically ill patients with known or suspected COVID–19, and discuss important alterations of the coagulation system in patients hospitalised due to COVID–19. Finally, we address special considerations pertaining to supply‐demand and cost‐benefit issues of patient blood management during the COVID–19 pandemic.